Comparison of routine cytology findings with conventional ziehl-neelsen method and fluorescent method for detection of acid fast bacilli in fine needle aspirates from suspected cases of tuberculous lymphadenitis - Dr. Alpeshpuri P. Goswami; Brahmbhatt, Smit; Khandkar, Abhijeet; Zinzala, Umesh; Gondliya, Jignesh; Goswami, Parth (Tropical Journal of Pathology and Microbiology, 2019)
Objective: This study aimed to correlate the modified fluorescence stain method and conventional ZN method with routine cytology findings on lymph node aspirates for the detection of AFB in suspected cases of tuberculous lymphadenitis. Material and Methods: After adequate fine needle aspiration, aspirates were examined for cytology diagnosis, studied with Ziehl-Neelsen and Auramine-rhodamine Fluorescent stain. Cytological findings, ZN stain observations and grading were compared with fluorescent stain grading. Result: In our study, 36 cases were reported positive by fluorescent staining method for M. tuberculosis. Out of 43 granulomatous lymphadenitis cases diagnosed by FNAC, 29 cases were reported positive for acid fast bacilli by Z-N staining. 11 cases were found as false negative (22%). Sensitivity and specificity of Z-N method was found to be 70.27% and 76.92% respectively. And for cytological method it was 96.77% and 31.57% respectively. Conclusion: There are problems in arriving at an absolute diagnosis in certain cases of tuberculous lymphadenitis when the aspirate shows polymorphous picture with occasional epithelioid cells and absence of typical Langhans giant cell or caseous necrosis. Microscopy has many advantages when it comes to speed & feasibility, its sensitivity could be improved by adjuvant methods.